La pre-mappatura dei disagi e dei pericoli professionali e la valutazione e gestione del rischio da sovraccarico biomeccanico: presentazione di uno strumento di analisi semplice e informatizzato (toolkit) e delle sue modalità di utilizzo / A preliminary mapping methodology for occupational hazards and biomechanical risk evaluation: presentation of a simple, computerized tool kit for ergonomic hazards identification and risk assessment - Colombini, D.; Occhipinti, E.; Di Leone, G. (La Medicina del Lavoro, 2011)
«A preliminary mapping methodology for occupational hazards and biomechanical risk evaluation: presentation of a simple, computerized tool kit for ergonomic hazards identification and risk assessment». Background and objectives: During the last Congress of the International Ergonomics Association (IEA), Beijing, August 2009, an international group was founded with the task of developing a “toolkit for MSD prevention” under the IEA and in collaboration with the World Health Organization. The possible users of toolkits are: members of health and safety committees; health and safety representatives; line supervisors; foremen; workers; government representatives; health workers providing basic occupational health services; occupational health and safety specialists. Methods: According to the ISO standard 11228 series and the new Draft CD ISO 12259-2009: Application document guides for the potential user, our group developed a preliminary “mapping” methodology of occupational hazards in the craft industry, supported  by  software (Excel®). Results and conclusion: The proposed methodology, using specific key enters and quick assessment criteria, allows a simple ergonomics hazards identification and risk estimation to be made. It is thus possible to decide for which occupational hazards a more exhaustive risk assessment will be necessary and which occupational consultant should be involved (occupational physician, safety engineer, industrial hygienist, etc.).